2016
DOI: 10.1007/s12603-016-0690-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between longevity and element levels in food and drinking water of typical Chinese longevity area

Abstract: The quality of food and water in Hainan Province are good and that, compared with water, food is a more important source of trace elements. An appropriate supply of Cu, Se, and Zn is important, whereas excessive intake of Pb should be avoided. The findings also provide basic data to support further studies on regional variations in longevity and their relationship to diet and drinking water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…This is because Se varied largely even at a small scale in soil, high Se content and low Se content usually coexist in a city, and the research scale of this paper is still too large to show relationship between Se and longevity. Some studies at the town scale and county scale within a city have shown that climate factors is almost the same, so Se will be more significant related to longevity [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because Se varied largely even at a small scale in soil, high Se content and low Se content usually coexist in a city, and the research scale of this paper is still too large to show relationship between Se and longevity. Some studies at the town scale and county scale within a city have shown that climate factors is almost the same, so Se will be more significant related to longevity [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, barium (Ba) and nickel (Ni) have significant negative correlations longevity, while distributions of cadmium (Cd), cobalt (Co), chromium (Cr), copper (Cu), manganese (Mn), vanadium (V), zinc (Zn), lithium (Li), and iron (Fe) showed no significant correlations with longevity [ 16 ]. Of all the trace elements, Se appears most closely linked with longevity [ 22 , 23 , 24 , 25 ]. Food contributes a greater proportion of daily elemental intake than drinking water [ 26 ], and the Se content in food is positively correlates with the Se content in soil [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Six out of the 19 drugs have already been reported to significantly extend the lifespan of at least one model organisms (S2 text), while only 1 was expected by chance (p < 0.001). Additionally, using literature mining, we identified studies showing the association with longevity of cAMP analogues [28], selenium [29,30] and tanespimycin [31,32]. In contrast, we also found evidence for the DNA-mediated, pro-ageing (anti-longevity) effects of doxorubicin [33], cisplatin [34] and hydrogen peroxide [35].…”
Section: Resultsmentioning
confidence: 99%
“…Details of this study have been described elsewhere [9]. The CHCCS is located in Hainan province, which is both a longevity area with the highest density of centenarians in China and an iodine sufficient region with abundant seafood provided [10]. Based on National Civil Registry, 1,002 centenarians were recruited in the present study.…”
Section: Study Populationmentioning
confidence: 99%